An association between excessive valgus hindfoot alignment and postural stability during single-leg standing in adolescent athletes - Yasunari Ikuta; Tomoyuki Nakasa; Hironori Fujishita; Hiromune Obayashi; Kouki Fukuhara; Tetsuhiko Sakamitsu; Kai Ushio; Nobuo Adachi (BMC, 2022)
Abstract Background Diminished balance is associated with the incidence of ankle and lower extremity injuries in adolescents. Although flexible flatfoot is a common foot condition in pediatric and adolescent populations, the association between balance control and foot morphology remain unclear in adolescent athletes. Methods Rearfoot angle in the double-limb standing position, body mass index (BMI), and isometric muscle strength related to the knee joint were retrospectively reviewed in 101 adolescent athletes (75 boys and 26 girls) with a mean age of 14.0 years (range 12-17). Postural stability during single-leg standing on static and dynamic platforms was investigated using Balance System SD in 119 feet without functional ankle instability. The participants were divided according to their rearfoot angle into control (less than 7°) and valgus (greater than or equal to 7°) groups. The measured parameters were compared between the control and valgus groups using Welch's t-test, and P values < 0.05 were considered statistically significant. Multiple regression analysis was conducted to identify the factors that significantly influenced postural control. Results The average rearfoot angle was 4.6° in all participants. An excessive valgus rearfoot angle was detected in 53 feet (26.2%). No significant difference was found between the groups in terms of BMI and isometric knee muscle strength. Although no statistical differences were observed in postural stability on the static platform between the control and valgus groups, the valgus group demonstrated poorer postural stability for single-leg standing on the dynamic platform. Multiple regression analysis revealed that BMI and rearfoot angle were significantly associated with a poor postural control on the dynamic platform. Conclusions Our findings suggest that excessive rearfoot valgus specifically contributes to the deterioration of postural stability in adolescent athletes, and that rearfoot alignment should be evaluated for the adolescent population to prevent sports-related lower extremity injury.